Desain konsep kendaraan roadster tahun 2050 yang menerapkan teknologi turbine engine - Geggy Gamal Surya; Khaola Rachma Adzima (Institut Seni Indonesia Yogyakarta, 2019)
The design in the next 30 to 100 years is a vision of industrial desainers to be able to provide an overview or exposure to the government, companies, industry players and the public, how this future product is projected (pictured) into a mature mind and can be realized according to provisions in his time. This depiction needs to be exploited through design education science. Without the knowledge of design education, thinking in this design cannot be described. Describe what is meant is